« ¡Santiago y cierra, España ! » - Lidwine Linares (Les Cahiers de Framespa)
« ¡Santiago y cierra, España! » is a battle cry well known in Spain and appears in many ancient and contemporary proverbs books. However it is often wrongly described, as for instance in José Calles and Belén Bermejo’s book, Expresiones y dichos populares, published in 2010. In this saying’s section, the medieval and legendary origins are claimed saying that « Apparently, the Apostle entrusted [King Ramiro] to close Hispania to the Muslims, what has been understood as block the way or complete the Reconquista, depending on the times ». Yet, the polysemy of the verb « cerrar » which also means « attack » has led to a misinterpretation of this cry, and, in some cases, to an inappropriate use. Also, contrary to what is said, this cry is not found in medieval texts, being a later development. Thus, it seemed interesting to make a historical journey of this cry and its use from its origins until today, and show how it is used and adapted to each era’s literature, politics and Spanish society.